DECENTRALIZATION AND INFRASTRUCTURE - Roca, Leonie (2022)
This article aims to analyze the relationship between decentralization and the infrastructure gap in Peru. In particular, the conditions in which decentralization has been carried out and how these impact investment in infrastructure will be analyzed. Likewise, statistical reports show where the deficiency in infrastructure is growing up and the gaps that exist between the departments in reference to this indicador. Concluding that investment in infrastructure must be promoted with good management by the central government and regional governments, as well as proposing mechanisms that allow the prioritization of the projects established until their completion and the commitment in the allocation of the necessary resources.